An overview on natural cholinesterase inhibitors - a multi-targeted drug class - and their mass production - Orhan, I. E.; Orhan, Gürdal; Gürka?s, Erdem (My University, 2011)
Cholinesterase enzyme family consisting of acetylcholinesterase (AChE) and butrylcholinesterase (BChE) is important in pathogenesis of Alzheimer's disease (AD), explained by "cholinergic hypothesis". Accordingly, deficiency of the neuromediator called "acetylcholine" excessive amount of BChE has been well-described in the brains of AD patients. Consequently, cholinesterase inhibition has become one of the most-prescribed treatment strategies for AD. In fact, cholinesterase inhibitors have been also reported for their effectiveness in some other diseases including glaucoma, myasthenia gravies, as well as Down syndrome, lately. They play a role in the action of mechanism of insecticidal drugs such as carbamate derivatives as well as nerve gases such as malathion and parathion. All these utilizations can make them a multi-targeted drug class putting a special emphasis on AD therapy in the first place. Several inhibitors of cholinesterases with synthetic and natural origins are available in drug market; however, the reasons including side effects, relatively low bioavailability, etc. limit their uses in medicine and there is still a great demand to discover new cholinesterase inhibitors. Galanthamine, an alkaloid derivative isolated from snowdrop (Galanthus nivalis L.), is the latest anticholinesterase drug used against AD. Huperzine A, isolated from Huperzia serrata (Thunb.) Trev. is the most-promising drug candidate with potent anticholinesterase effect and it is a licensed anti-AD drug in China. In this review, a short introduction will be given on known cholinesterase inhibitors and, then, galanthamine and huperzine A will be covered in regard with their cholinesterase inhibitory potentials and mass productions by organic synthesis and in vitro culture techniques. © 2011 Bentham Science Publishers Ltd.
Keywords: Acetylcholinesterase; Alzheimer's disease; Butyrylcholinesterase; Cholinesterase inhibition; Galanthamine; Huperzine a; In vitro plant culture; Organic synthesis